Immediate effects of lavender soy wax candle on autonomic nervous system, stress, and reaction time in adolescents - Hanphitakphong Panida; Poomsalood Somruthai (Sciendo, 2024)
Study aim: The study aimed to investigate the immediate effects of a lavender soy wax candle on the autonomic nervous system, stress, and reaction time in adolescents with moderate stress levels.